The deadly impact of COVID-19 among children from Latin America: The case of Ecuador - Ortiz-Prado, Esteban; Izquierdo-Condoy, Juan S.; Fernandez-Naranjo, Raul; Vasconez, Jorge; Dávila Rosero, María Gabriela; Revelo-Bastidas, Doménica; Herrería-Quiñonez, Diva; Rubio-Neira, Mario (Frontiers in Pediatrics, 2023)
Background The SARS-CoV-2 pandemic remains a critical global health concern, with older adults being the most vulnerable group. Nonetheless, it is crucial to recognize that COVID-19 has caused numerous deaths in children worldwide. Emerging evidence indicates that infants and breastfeeding children, particularly those aged below one year, face a greater risk of hospitalization and mortality than older children with COVID-19. Objective: This study aimed to describe the epidemiology of COVID-19 among children during the early phase of the pandemic in Ecuador. Methods We conducted a country-wide population-based analysis of the epidemiology of COVID-19, using incidence and mortality data reported from Ecuador between February 15th, 2020, and May 14th , 2021. Measurements of frequency, central tendency, dispersion, and absolute differences were calculated for all categorical and continuous variables. Results At least 34,001 cases (23,587 confirmed cases, 5,315 probable and 5,099 suspected) and 258 COVID-19 related deaths have been reported among children in Ecuador during the first 16 months of the pandemic. The overall incidence rate was 612 cases per 100,000 children, the mortality rate was 3 per 100,000, while the case fatality rate was 0.76%. The highest risk group for infection was children and adolescents between 15 and 19 years of age; however, the highest mortality rate occurred in children under one year of age. The largest provinces, such as Pichincha, Guavas and Manabí, were the ones that reported the highest number of cases, 27%, 12.1% and 10.8%, respectively. Conclusions This study is the first to report on COVID-19 epidemics among children in Ecuador. Our findings reveal that younger children have a lower risk of SARS-CoV-2 infection, but a higher risk of mortality compared to older children and adolescents. Additionally, we observed significant disparities in infection rates and outcomes among children living in rural areas, those with comorbidities, and those from indigenous ethnic groups.